2022
DOI: 10.3389/fnut.2022.934518
|View full text |Cite
|
Sign up to set email alerts
|

Litchi flower essential oil balanced lipid metabolism through the regulation of DAF-2/IIS, MDT-15/SBP-1, and MDT-15/NHR-49 pathway

Abstract: Many litchi flowers are discarded in China every year. The litchi flower is rich in volatile compounds and exhibits strong anti-obesity activity. Litchi flower essential oil (LFEO) was extracted by the continuous phase transformation device (CPTD) independently developed by our research group to recycle the precious material resources in litchi flowers. However, its fat-reducing effect and mechanism remain unclear. Employing Caenorhabditis elegans as a model, we found that LFEO significantly reduced fat storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…Caenorhabditis elegans (C. elegans) has highly conserved genes with humans, a transparent body, and an affluent population of gene defect mutations, making it an excellent model for studying lipid metabolism 13) . Research has found that some edible oils, such as litchi flower essential oil 14) and salvia miltiorrhiza seed oil 15) , can reduce the lipid accumulation of C. elegans, improve its lipid metabolism, and reduce obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Caenorhabditis elegans (C. elegans) has highly conserved genes with humans, a transparent body, and an affluent population of gene defect mutations, making it an excellent model for studying lipid metabolism 13) . Research has found that some edible oils, such as litchi flower essential oil 14) and salvia miltiorrhiza seed oil 15) , can reduce the lipid accumulation of C. elegans, improve its lipid metabolism, and reduce obesity.…”
Section: Introductionmentioning
confidence: 99%